Factors influencing the occurrence of the Endangered Baird's tapir Tapirus bairdii: Potential flagship species for a Costa Rican biological corridor - Spínola, Romeo (2014)
Baird’s tapir Tapirus bairdii is categorized as Endangered on the IUCN Red List and is considered rare and locally extirpated from most of its historic range in Costa Rica. We conducted camera-trap and track surveys at 38 forested sites in and around the San Juan–La Selva Biological Corridor in the Northern Zone of Costa Rica. Cameras were set along established game trails and natural funnels and operated for 14–38 days per site. Additionally, we documented tapir tracks at many sites. We used survey photographs and track presence to create detection histories to estimate the habitat and survey-specific variables that influence the probability of detection and the probability of occurrence of Baird’s tapir. The two major protected areas within and adjacent to the corridor were most positively associated with tapir occurrence, and forest cover and native and exotic tree plantations were also positively associated with tapirs’ use of sites. Although the Baird’s tapir is rare, our findings suggest that it is more resilient and better able to use available habitat in the fragmented corridor than previously thought. This is most likely a consequence of increased forest cover from reforestation and tree plantations and limited hunting pressure. Given its charismatic nature we recommend that Baird’s tapir could be used as a flagship species for the San Juan–La Selva Biological Corridor, to raise local awareness about conservation and increase economic growth from ecotourism.